DECISION PROCESSES WITH SELF-ADMINISTERED AND LIMITED TIME: ¿A ADAPTATIVE RESPONSE TO SIMILARITY, FORMAT AND EXPERIENCE? - Iglesias Parro, Sergio; De la Fuente Solana, Emilia Inmaculada; García García, Juan; De la Fuente Sánchez, Leticia (Anales de Psicología / Annals of Psychology, 2001)
The main objective of this paper is to study the possible effect exerted by the interaction of task, subject and context variables on cognitive effort and on the decisionstrategy in tasks of multiattribute choice with two alternatives. To this end, we carried out two experiments in which we simultaneously manipulated the Format of information presentation, the Similarity between the alternatives of the choice group and the subjects’ Experience with the tasks under conditions of self-administered time (Experiment 1) and under conditions of time pressure (Experiment 2). The results of both experiments evince that there exist interactions among these variables and that the interaction among the variables of interest affects cognitive effort, measured by means of direct activity indicators. The data obtained equally indicate that this effect is different depending on the availability of time to perform the tasks. Nevertheless, the cognitive effort evaluated through selfreports was, in both experiments, quite low, something which might explain the absence of change in the decision strategies implemented by the subjects.